Association of muscle strength with muscle thickness and motor unit firing pattern of vastus lateralis muscle in youth athletes - Yoshimura, A.; Kunugi, S.; Hirono, T.; Nojima, H.; Ueda, S.; Holobar, A.; Mita, Y.; Watanabe, K. (International Journal of Sports Physiology and Performance, 2022)
Purpose: Contributions of neural and muscular factors to muscle strength change with growth, but such changes remain unclear in young populations. This study aimed to clarify the association between muscle strength and neural and muscular factors in youth athletes.